Autorytarne prawa naturalne? Kilka uwag o negatywnym potencjale pozytywnych idei - Łuszczyńska, Małgorzata; Łuszczyński, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article presents authors’ reflection upon the problem of the law of nature. In the literature on the subject, there is adominant opinion that the natural law is atype of amatrix, which should be duplicated by the legislator in order to prevent unfair laws. Following the Latin maxim: “Lex iniusta non est lex” “Unfair law is not alaw”, legislator must take into account all non-specified norms of the higher order. According to the authors of this article, in the modern times the natural law rationalism is rather apparent, and its religious foundations will not necessarily be accepted in the culturally plural [multicultural?] society.
Keywords: prawo natury; autorytet; aksjologia